Pd(II)-Catalyzed Phosphorylation of Aryl C–H Bonds - Feng, Chen-Guo; Ye, Mengchun; Xiao, Kai-Jiong; Li, Suhua; Yu, Jin-Quan (Journal of the American Chemical Society, 2013)
A Pd(II)-catalyzed C–H phosphorylation reaction has been developed using heterocycle-directed ortho-palladation. Both H-phosphonates and diaryl phosphine oxides are suitable coupling partners for this reaction.